James Allen Hardie papers - Hardie, James Allen, 1823-1876.
Correspondence, memoranda, reports, orders, financial papers, and printed matter relating primarily to Hardie's military service in the West both during and following the Civil War. Subjects include the Mexican War, military affairs in California and Oregon (1847-1860), the Civil War especially the transfer of the command of the U.S. Army of the Potomac from Joseph Hooker to George Gordon Meade prior to the Battle of Gettysburg, the assassination of Abraham Lincoln, the execution of Mary E. Surratt in 1865, and Indian affairs in Montana and the Northwest. Correspondents include Orville Elias Babcock, Ambrose Everett Burnside, H.W. Halleck, Rufus Ingalls, Randolph Barnes Marcy, Philip Henry Sheridan, William T. Sherman, M.J. Spalding, E.D. Townsend, John Ellis Wool, and George Wright.
Army officer.
Collection material in English.
Keywords: Babcock, Orville Elias, -- 1835-1884 -- Correspondence; Burnside, Ambrose Everett, -- 1824-1881 -- Correspondence; Halleck, H. W. -- 1815-1872 -- Correspondence; Hooker, Joseph, -- 1814-1879.; Ingalls, Rufus, -- 1818-1893 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Marcy, Randolph Barnes, -- 1812-1887 -- Correspondence; Meade, George Gordon, -- 1815-1872.; Sheridan, Philip Henry, -- 1831-1888 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Spalding, M. J. -- 1810-1872 -- Correspondence; Surratt, Mary E. -- 1820-1865.; Townsend, E. D. -- 1817-1893 -- Correspondence; Wool, John Ellis, -- 1784-1869 -- Correspondence; Wright, George, -- 1803-1865 -- Correspondence; United States. -- Army of the Potomac; Indians of North America -- Montana; Indians of North America -- Northwestern States; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Mexican War, 1846-1848.; California -- History, Military; Oregon -- History, Military; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; West (U.S.) -- History -- Civil War, 1861-1865.; West (U.S.) -- History, Military; Army officers